2006
DOI: 10.1203/01.pdr.0000219431.45075.d9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chymase-Dependent Angiotensin II Formation in Monocrotaline-Induced Pulmonary Hypertensive Rats

Abstract: Angiotensin II-forming chymase is expressed in the pulmonary arteries of the monocrotaline-induced pulmonary hypertensive rats, but its actual role is unclear. We studied chymasedependent angiotensin II formation in the pulmonary arteries of the monocrotaline-induced pulmonary hypertensive rats and observed the effects of an angiotensin II receptor blocker on vascular remodeling. Four weeks after the administration of monocrotaline (60 mg/kg, s.q.), echocardiographic, hemodynamic, morphometric and biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…Losartan (10 mg/kg per day) did not inhibit monocrotaline-induced pulmonary hypertension and RV hypertrophy (14). On the other hands, Kishi et al reported that candesartan (10 mg/kg per day) prevented the decrease of AT, the increase of pulmonary arterial pressure, and RV hypertrophy induced by monocrotaline treatment (15). The present study demonstrated that telmisartan did not improve the decrease of AT /ET ratio, but attenuated RV hypertrophy.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Losartan (10 mg/kg per day) did not inhibit monocrotaline-induced pulmonary hypertension and RV hypertrophy (14). On the other hands, Kishi et al reported that candesartan (10 mg/kg per day) prevented the decrease of AT, the increase of pulmonary arterial pressure, and RV hypertrophy induced by monocrotaline treatment (15). The present study demonstrated that telmisartan did not improve the decrease of AT /ET ratio, but attenuated RV hypertrophy.…”
Section: Discussioncontrasting
confidence: 52%
“…The effects of angiotensin II type 1 receptor (AT1R) blockers in monocrotalineinduced RV hypertrophy have not yet been completely clarified. Losartan did not inhibit monocrotalineinduced RV hypertrophy (14), while candesartan prevented it (15). Telmisartan, a 5th generation AT1R blocker, is used for the treatment of hypertension and has cardioprotective effects (16).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that the Ang II generating chymase gene is expressed in rat vascular tissues. In this regard, we also confirmed that Ang II producing chymase is high in lung arteries of drug-induced pulmonary hypertensive rats (33).…”
Section: Chymase-dependent Tissue Ang II and Related Pathologysupporting
confidence: 79%
“…The involvement of mast cells in the development of PAH has received little attention, although they may be of specific interest since mast cells are known as potent angiogenic stimulators (8,24). Mast cells may play a role in angiotensin II-mediated vasoconstriction (18), supposedly via specific serine proteases from their granules (14,21). Chymase, one of the serine proteases excreted by mast cells, is involved in the conversion of angiotensin I to angiotensin II (18) and of big endothelin to endothelin-1 (9), two powerful vasoconstrictors with mitogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells may play a role in angiotensin II-mediated vasoconstriction (18), supposedly via specific serine proteases from their granules (14,21). Chymase, one of the serine proteases excreted by mast cells, is involved in the conversion of angiotensin I to angiotensin II (18) and of big endothelin to endothelin-1 (9), two powerful vasoconstrictors with mitogenic properties. Together, these data suggest that the presence of excessive mast cells in pulmonary arteries of human and experimental PAH contributes to the development of the disease.…”
Section: Discussionmentioning
confidence: 99%